PEMELIHARAAN LARVA UDANG VANNAMEI (Litopenaeus vannamei) DENGAN GENETIKA BERBEDA - Subhan, Rio Yusufi; Witoko, Pindo; Kurniawan, Ilham Hadi (Jurnal Perikanan Terapan, 2023)
Vannamei shrimp is a prospective commodity that continues to be cultured intensively in Indonesia. Efforts to produce vannamei shrimp fry are an activity that continues to be developed by stakeholders, including efforts to improve genetics. Apart from a good aquaculture system, genetics is also an important factor in the success of vannamei shrimp culture. This research was conducted at CV. Manunggal Rasa with a research design carried out using a comparison of 2 genetics of vannamei shrimp larvae, namely American Penaeid, Inc (API) and Benchmark Genetics (BM) with a stocking density used of 40,000 individuals/m2 in each pond with an area of 25 m2. Rearing vannamei shrimp fry for 4 cycles provided several differences in the observation of absolute length growth and survival rate. The absolute length growth of the API genetic vannamei shrimp fry was 5.68 mm, while the BM genetics was 6.16 mm. The survival rate in each cycle is cycle 1 (API 89.9% and BM 93.1%), cycle 2 (API 91.4% and BM 95.6%), cycle 3 (API 88.9% and BM 89 .7%) and cycle 4 (API 93.2% and BM 94.6%). The water quality for each cycle is calculated to be optimal, namely ranging from 27-31oC (temperature), 4.5-5 ppm (DO), 30 ppt (salinity), 0-0.1 ppm (ammonia) and 7.9-8.3 (pH).